2001
DOI: 10.1111/1469-8986.3840712
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the human nociceptive flexion reflex across the cardiac cycle

Abstract: Carotid baroreceptor stimulation has been shown to dampen pain. This study tested, in 40 normotensive adults, the hypothesis that pain is lower during systole when arterial baroreceptor stimulation is maximal than diastole when stimulation is minimal. The sural nerve was stimulated electrocutaneously to obtain a nociceptive flexion reflex (NFR) threshold, and then stimulation was delivered for 28 trials at 100% NFR threshold at seven intervals after the R-wave. Nociceptive responding was indexed by electromyog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
83
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 108 publications
(101 citation statements)
references
References 37 publications
17
83
1
Order By: Relevance
“…Specifically, the NFR was facilitated by the distracting and arousing computer game task, Tetris ® , while pain was attenuated. Such a dissociation between pain and the NFR has been noted previously (e.g., Andersen et al, 1995;Bouhassira et al, 2003;Edwards et al, 2001Edwards et al, ,2002Edwards et al, ,2003aEdwards et al, ,2006McIntyre et al, 2006;Terkelsen et al, 2004;Willer et al, 1979). In addition, a similar dissociation has been recently reported between pain and the nociceptive blink reflex during psychological arousal (Koh and Drummond, 2006).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Specifically, the NFR was facilitated by the distracting and arousing computer game task, Tetris ® , while pain was attenuated. Such a dissociation between pain and the NFR has been noted previously (e.g., Andersen et al, 1995;Bouhassira et al, 2003;Edwards et al, 2001Edwards et al, ,2002Edwards et al, ,2003aEdwards et al, ,2006McIntyre et al, 2006;Terkelsen et al, 2004;Willer et al, 1979). In addition, a similar dissociation has been recently reported between pain and the nociceptive blink reflex during psychological arousal (Koh and Drummond, 2006).…”
Section: Discussionsupporting
confidence: 80%
“…In humans, the evidence in favour of opioid dysfunction is mostly negative (e.g., Bruehl et al, 2002;France et al, 2005;Ring et al, 2007;Schobel et al, 1998;cf. McCubbin and Bruehl, 1994;McCubbin et al, 2006) whereas the evidence for baroreceptor activation is more mixed (e.g., al 'Absi et al, 2005;Edwards et al, 2001Edwards et al, ,2003aGuasti, Zanotta, Mainardi, et al, 2002;McIntyre et al, 2006;Rau et al, 1995). Although the current experiments were designed to investigate the function of the descending pain modulation systems in essential hypertension and risk for hypertension, results indicated that there were no differential effects on nociception or pain.…”
Section: Discussionmentioning
confidence: 99%
“…For example, pain catastrophizing is associated with elevated negative affect (Hirsh et al 2007), which in turn is often associated with heightened cardiovascular stress reactivity (Burns 1995;Feldman et al 1999;Kamarck et al 1998;Prkachin et al 1999). Prior work indicates that elevations in systolic blood pressure trigger endogenous analgesic mechanisms through functional links between the cardiovascular and pain regulatory systems (e.g., Bruehl and Chung 2004;Edwards et al 2001Edwards et al , 2003Ghione 1996;Rau and Elbert 2001). In this context, a mediation model would predict that catastrophizing would be associated with lower pain intensity through activation of blood pressure-related analgesia.…”
Section: Introductionmentioning
confidence: 99%
“…The hyperalgesic effects of this profile can be interpreted in light of literature regarding blood pressure-related analgesia. Elevated resting blood pressure is reliably associated with reduced acute pain responsiveness (Bruehl et al 1992;Ghione 1996), and evidence suggests that transient increases in systolic blood pressure also elicit hypoalgesia (Edwards et al 2001;. Individuals who are prone to catastrophize about pain who also exhibit low stress-induced cardiovascular reactivity may experience greater daily chronic pain intensity due to automatic negative appraisals of pain stimuli in combination with limited activation of blood pressure-related antinociceptive mechanisms.…”
mentioning
confidence: 99%
“…A 4-2-1 up-down staircase method was used to determine the nociceptive flexion reflex threshold (Edwards et al, 2001). The sural nerve was stimulated by five 1-ms square-wave pulses at 250 Hz.…”
Section: Nociceptive Flexion Reflex Thresholdmentioning
confidence: 99%